On The Performance Of Technology-Sourcing Partnerships: The Interaction Between Partner Interdependence And Technology Attributes - Steensma, H. Kevin; Corley, Kevin G. (Academy of Management Journal, 2000)
This study examines the outcomes of technology-sourcing partnerships from the sourcing firms' point of view. Using a knowledge-based perspective, the authors develop a contingency model suggesting how the imitability, uniqueness, and uncertainty associated with a technology interact with partner interdependence to influence sourcing outcomes. Ninety-five sourcing arrangements spanning licensing, joint development, and acquisitions were examined close to the time of conception and three to four years afterward. Overall, the results support a contingency framework.